Diseño y construcción de un prototipo de máquina mezcladora de pintura semiautomatizada. - Domínguez Santín, Diego Fernando (2011)
The present investigation has as end to develop the Design of an automated prototype that obtains different colors being based on the chromatic circle, having as purpose to endow of one it schemes didactics to the laboratory of Automation of the National University of Loja, with which the students of the career of Electromechanical Engineering can appreciate the use of a programmable robot, sensor of ultrasonic and a pneumatic system, operating on the whole inside a real process. As first part of the investigation it is presented the automated processes, the manual processes of the production of painting at international, national and local level. Continuing with the development of the thesis is explained how the prototype automated in its mechanical structure, pneumatic system and the electric system is designed. Next the design of the control system was explained next to the selection of all its elements that you/they compose the same one. Starting from here the programming is indicated implemented for the system of control of the machine prototype, indicating the function of each one on its behalves inside the automated process.